2022
DOI: 10.1101/2022.02.22.481100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitoquinone mesylate targets SARS-CoV-2 infection in preclinical models

Abstract: To date, there is no effective oral antiviral against SARS-CoV-2 that is also anti-inflammatory. Herein, we show that the mitochondrial antioxidant mitoquinone/mitoquinol mesylate (Mito-MES), a dietary supplement, has potent antiviral activity against SARS-CoV-2 and its variants of concern in vitro and in vivo. Mito-MES had nanomolar in vitro antiviral potency against the Beta and Delta SARS-CoV-2 variants as well as the murine hepatitis virus (MHV-A59). Mito-MES given in SARS-CoV-2 infected K18-hACE2 mice thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(149 reference statements)
1
1
0
Order By: Relevance
“…Specifically, the Spike infection significantly decreased basal respiration (0.52-fold in Spike vs VSV-G, P = 0.0034) ( Fig. 5D ), which was similar to the effect of SCV2 infection in Calu3 cells as compared to the uninfected cells ( 29 ). Particularly, maximal respiration (0.5-fold in Spike vs VSV-G, P = 0.0032) ( Fig.…”
Section: Resultssupporting
confidence: 70%
“…Specifically, the Spike infection significantly decreased basal respiration (0.52-fold in Spike vs VSV-G, P = 0.0034) ( Fig. 5D ), which was similar to the effect of SCV2 infection in Calu3 cells as compared to the uninfected cells ( 29 ). Particularly, maximal respiration (0.5-fold in Spike vs VSV-G, P = 0.0032) ( Fig.…”
Section: Resultssupporting
confidence: 70%
“…After administration of oral supplementation with MitoQ the patients with impaired endothelial function improved brachial artery flow-mediated dilation, aortic stiffness, and plasma oxidized low-density lipoprotein ( 37 , 38 ). A preprint study showed MitoQ and mitoquinol mesylate could play an anti-inflammatory and antiviral role through its mitochondrial antioxidant properties ( 39 ). Although MitoQ can reduce pulmonary damage in vitro and in vivo, but the clinical trials showing that MitoQ treats or protects the pulmonary disease are still lacking ( 26 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial oxidative stress can also be reduced using mitochondrion-targeted catalytic antioxidants such as MnTBAP [188], EUK-8, and EUK-134 [189], as well as Mito-TEMPO and mitoquinol [112,162,190]. In addition, mitochondrial quinone/mitochondrial phenol mesylate (Mito-MES) has been demonstrated to possess significant antiviral activity against SARS-CoV-2 and can reduce excessive inflammation in the host [191]. Effective treatment can also be obtained with mPTP inhibitors such as NIM811 [192,193].…”
Section: Therapeutic Strategies Against Covid-19 Involving Mitochondriamentioning
confidence: 99%